2018
DOI: 10.3390/geosciences8070256
|View full text |Cite
|
Sign up to set email alerts
|

The Majella National Park: An Aspiring UNESCO Geopark

Abstract: Majella National Park is located in the central Apennines (Italy), in a vast mountainous area of about 740 km 2. Owing to the complex geological history of the Majella Massif and surrounding areas, it features many different landforms. Woodlands rich in water characterize the wide tectonic depression of Caramanico, which separates the rounded gentle profile of the Majella to the east from the impervious steep slope of the Morrone Mt. to the west. Bare pitted highlands, like lunar landforms, characterize the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The selection of the path and the main stop sites was qualitatively based on three main criteria similar for archeology and geology: (i) location and spatial connection along the Terre Peligne area; (ii) site type and origin, and (iii) temporal distribution in the geological/archeological time scale [28,[40][41][42]. Even if at this stage we did not run a quantitative assessment of the sites [20], this approach is in agreement with what has been done in many cases for geosites evaluation (e.g., within Environmental Impact Assessment and territorial planning [11,12,43]; inventories of natural heritage sites, [31,35,40,44]; tourist promotion [14,45]; management of nature parks [4,6,22,46,47]).…”
Section: Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…The selection of the path and the main stop sites was qualitatively based on three main criteria similar for archeology and geology: (i) location and spatial connection along the Terre Peligne area; (ii) site type and origin, and (iii) temporal distribution in the geological/archeological time scale [28,[40][41][42]. Even if at this stage we did not run a quantitative assessment of the sites [20], this approach is in agreement with what has been done in many cases for geosites evaluation (e.g., within Environmental Impact Assessment and territorial planning [11,12,43]; inventories of natural heritage sites, [31,35,40,44]; tourist promotion [14,45]; management of nature parks [4,6,22,46,47]).…”
Section: Methodsmentioning
confidence: 61%
“…The purpose of the study is in line with the stream of similar initiatives aimed at the knowledge, valorization, and fruition of the internal mountain areas. Just to remain within the Abruzzo region, among many others see the cases within the Parks of Majella and Velino-Sirente [6,85], or the case of the APSAT (Ambiente e Paesaggi dei Siti d'Altura Trentini) Project for the Trentino region [86] or the transhumance route in southern Italy [87] at international level (e.g., Egypt, Russia, Malta [7,88,89]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UNESCO Global Geoparks Villuercas-Ibores-Jara contributes to this training by creating routes between geosites [85]. Several studies, such as that of Liberatoscioli et al [86] or Rivero et al [87], have shown that these infrastructures are positively valued by visitors because its help them to learn about geology. Moreover, geoparks need to incorporate new technologies in order to promote the learning-process amongst its visitors.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, their consideration is necessary to diversify conservation and recreation activities in geoparks while on the other hand, these 'auxiliary' natural elements have to be protected from excessive exploitation of geological heritage resource. For instance, water resources have become the subject of analysis in the Langkawi geopark in Malaysia [17], the Majella geopark in Italy [18], and the Luoping Biota geopark in China [19]. More generally, it is possible to state that geoparks represent geological heritage landscapes (sensu [20]), i.e., landscapes dominated by unique geological features, but not restricted to them.…”
Section: Introductionmentioning
confidence: 99%